Transmittance Characterization of Objective Lenses Covering all Four Near Infrared Optical Windows and its Application to Three-Photon Microscopy Excited at 1820 nm - Ke Wang; Wenhui Wen; Hongji Liu; Yu Du; Ziwei Zhuang; Ping Qiu (IEEE Photonics Journal)
Near infrared (NIR) excitation or emission is capable of deep-tissue penetration in various modalities of optical microscopy. Based on the transmittance characterization of biological tissue, such as brains, four NIR optical windows have been demonstrated or suggested: The 800-nm, the 1300-nm, the 1700-nm, and the 2200-nm window. High-numerical aperture objective lenses are needed in optical microscopy to both deliver sufficient excitation light and collect efficient signal light to enable deep-tissue imaging. The transmittance performances of objective lenses are of vital importance. However, there is a lack of experimental characterization of the transmittance, especially at long wavelengths, which poses a dramatic obstacle for lens selection in imaging experiments. Here, we demonstrate detailed measurement results of the transmittance performance of air, water-immersion, and oil-immersion objectives available to us, covering all the four NIR optical windows. These results will provide direct guidelines for objective lens selection in terms of transmittance performance. We further demonstrate three-photon microscopy with 1820-nm excitation, close to the edge of the 1700-nm window, using the objective lens based on our transmittance measurement.